Ceria nanoparticles uniformly decorated on graphene nanosheets with coral-like morphology for high-performance supercapacitors. (June 2016) - Tao, Yan; Ruiyi, Li; Haiyan, Zhu; Zaijun, Li
Graphical abstract: The study reported the synthesis of coral-like CeO2 /GNs for supercapacitors. The unique architecture with overall connected framework and good conducting network of the graphene greatly boosts the Faradaic redox reaction. Therefore, the CeO2 /GNs delivers an excellent electrochemical performance. Highlights: The study reported the synthesis of CeO2 /GNs. The graphene was woven into CeO2, acting as a good conducting network. The CeO2 /GNs shows a coral-like structure. The architecture creates an overall connected framework. The CeO2 /GNs delivers good capacitive performances. Abstract: CeO2 /graphene was synthesized by a simple microwave method along with subsequent calcination. CeO2 nanoparticles with an average size of 68.8 nm are uniformly decorated on graphene nanosheets (CeO2 /GNs). The CeO2 /GNs displays a like-coral morphology. The architecture including overall connected framework, abundant intercrossed and interconnected nanochannels and perfect conducting network of the graphene, endows the CeO2 /GNs material with a superior electron and mass transport. As a result, the CeO2 /GNs gives a high specific capacitance of 503.4 F/g at 2 A/g and good cycle performance with 91.8% capacitance retention after 3000 cycles. Further, an asymmetric supercapacitors was assembled by using CeO2 /GNs as the positive electrode and activated carbon as the negative electrode, the asymmetric device demonstrate a favorable energy density of 30.2 Wh/kg at the power density of 750.0 W/kg and superior cycle life with 86.4% the capacitance retenion at 5 A/g after 3000 cycles.